What It’s Worth – A Review of Mineral Royalty Information (44df29f6-3600-488d-9223-463d93932568) - H. Lyn Bourne (Society for Mining, Metallurgy & Exploration, 1990)
This is the eighth annual tabulation of royalty information. Again this year, some of the older information has been deleted to make room for nearly 30 new entries. Several articles and publications have appeared recently that relate to mineral royalty or mineral valuation. R. B. Parsons wrote "Mining agreements, royalties and profits" (CIM Bulletin, November 1988). He distinguished between net smelter return (NSR) and net profit interest (NPI). Parsons used examples to show the difference between these royalty payment methods. Mining Engineering (January 1990) carried an article by H. V. S. Tingley entitled "Using business due diligence to help evaluate mineral deposits." The article identifies some factors that must be examined during mergers or acquisitions in the mining industry. Since each mining operation is unique, each has risks and opportunities that need recognition and evaluation. The author suggests that a team is necessary for a proper evaluation because no one person has expertise in all of the factors that must be examined. Also in January's Mining Engineering was "Limestone mining: Reserves and valuation," by B. C. Lewis and R. P. Moran. They presented two case studies of valuation of limestone reserves. One was a 109-hm2 (270-acre) parcel in West Virginia and the other a 121-hm2 (300-acre) tract in Alabama. The authors discussed risk, discount rates, and royalty methods as financial parameters in valuation of limestone reserves. Two papers were presented at the SME meeting in Las Vegas, NV in 1989 that bear mention. J.G. Russell's talk was entitled "Valuation of industrial